Law of affidavits: With more than 200 model forms of affidavits - Parameswaran,S (India Unversal Law Publishing Co.Pvt.Ltd, 2013)
The book puts forward the enormous and many-sided literature on affidavits spread over different statutes in India and brings to the readers the quintessence of judicial dicta concerning affidavits laid down in myriad of cases decided by the Indian courts with reference to well-known English and American decided cases in order to make it an extensive work. The book is also useful to the judges, lawyers, administrators and would also help laymen understand the law of affidavit better.
Include Index
ocf,07/06/19
Loans
Keywords: Law of Affidavit; law of evidence